IDIOM DALAM BAHASA MELAYU DIALEK PONTIANAK KALIMANTAN BARAT - Tria Widarti; Hotma Simanjuntak; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractIn this context, the researcher analyzed idiom in Pontianak Dialect Malay. This study was focused on the scope of problems in forms, types, meanings, and functions of idiom in Pontianak Dialect Malay. This study was aimed to describe the forms, types, meanings, and functions of idiom in Pontianak Dialect Malay. Qualitative descriptive method is used as a form of research. The data used are texts from recorded interviews, the video of Pontianak dialect Malay language, and textbooks. Data collection techniques used are listening, recording, note-taking, and documentary study techniques. Data collection tools in this study are a list of questions, record tools, and stationery. The findings show that idiom is divided into two forms: mono-morphemes and poly-morphemes. Poly-morphemes is classified into affixation, reduplication, compounding, and phrase. The types of idiom are classified into full and partial idiom. The meaning of the idiom is a figurative meaning differed from its lexical meaning elements in the context of the sentence. Lastly, the functions of idiom were analyzed based on the functions in sentences, and in social contexts. Keywords: forms,  function of idiom, meaning,  type